Liberating the open and distance learning model from the chains of oppressive education theories - Mackenzie Ishmael Chibambo; Joseph Jinja Divala; Aggripa Chingombe (Frontiers in Education)
This study argues that open and distance learning (ODL) continues to function as a platform for producing factory-like workers and white-collar laborers whose primary function is to serve the capitalist labor market. The study draws on Bowles and Gintis’ correspondence theory, as well as the Factory Education Model (FEM), and the Industrialized Teaching Model (ITEM) by Otto Peters, as theoretical propositions to explain how schooling contexts and the hidden curriculum prepare students the interests of employers (capitalists) and the powerful elites of modern society. While the findings of this study are applicable across various higher education contexts, ODL has significantly demonstrated a strong alignment with the predictions of the correspondence theory, FEM and ITEM, probably due to its mode of delivery and historical foundations. While some scholars may find these parallels unremarkable, the reality remains that existing ODL policies and practices continue to perpetuate epistemological injustices, stifling human agency, and curtailing various freedoms. Based on this, this study has proposed educational practices that are grounded in the principles of engaged and critical pedagogy, as advocated by Paulo Freire and bell hooks, as the most effective means of countering the harms perpetuated by FEM and ITEM. Methodologically, this study utilized a qualitative research design using critical hermeneutics, along with discourse analyses, observations, and lived experiences. Critical hermeneutics was chosen for its ability to reveal power relations and ideologies that perpetuate hegemony, domination, exploitation, and control over powerless individuals.